Imprinting of maternal thyroid hormones in the offspring. (4th July 2017) - Opazo, María Cecilia; Haensgen, Henny; Bohmwald, Karen; Venegas, Luis F.; Boudin, Helene; Elorza, Alvaro A.; Simon, Felipe; Fardella, Carlos; Bueno, Susan M.; Kalergis, Alexis M.; Riedel, Claudia A.
ABSTRACT: Thyroid hormones (THs) during pregnancy contribute significantly to cellular differentiation and development in several tissues of the offspring, principally the central nervous system (CNS). TH deficiencies, such as hypothyroidism or hypothyroxinemia, are highly frequent during pregnancy worldwide and known to be detrimental for the development of the fetus. The function of CNS in the offspring gestated under TH deficiency will be irreversible impaired, causing low intellectual quotient, attention deficit, and mental retardation. On the other hand, little is known about the effects of TH deficiency in the offspring immune system, being the prevalent notion that the effects are reversible and only for a while will affect the number of B and T cells. Recent studies have shown that maternal hypothyroidism can altered the function of immune system in the offspring, rendering the female offspring more susceptible to suffer autoimmune-inflammatory diseases, such as experimental autoimmune encephalomyelitis (EAE) and to be more resistant to a bacterial infection. In this article we discuss these recent findings, as well as the possible mechanisms underlying these effects and the potential implications for human health.